Current status and historical variations of DDT-related contaminants in the sediments of Lake Chaohu in China and their influencing factors. (December 2016) - Kang, Lei; He, Qi-Shuang; He, Wei; Kong, Xiang-Zhen; Liu, Wen-Xiu; Wu, Wen-Jing; Li, Yi-Long; Lan, Xin-Yu; Xu, Fu-Liu
Abstract: The temporal-spatial distributions of DDT-related contaminants (DDXs), including DDT (dichlorodiphenyltrichloroethane), DDE (dichlorodiphenyldichloroethylene) and DDD (dichlorodiphenyldichloroethane), in the sediments of Lake Chaohu and their influencing factors were studied. p, p-DDE and p, p-DDD were found to be the two dominant components of DDXs in both surface and core sediments. The parent DDT compounds were still detectable in sediment cores after the late 1930s. Historical usage of technical DDT was identified as the primary source of DDXs in sediments, as indicated by DDT/(DDD + DDE) ratios of less than one. The residual levels of DDXs were higher in the surface and core sediments in the western lake area than in other lake areas, which might be due to the combined inflow effects of municipal sewage, industrial wastewater and agricultural runoff. The DDX residues in the sediment cores reached peak values in the late 1970s or early 1980s. There were significant positive relationships between DDX residues in sediment cores with annual DDT production and with fine particulate sizes (<4.5 μm). The relationship between the DDXs and TOC in sediment was complex, as indicated by the significant differences among the surface and core sediments. The algae-derived organic matter significantly influenced the amount of residue, composition and distribution of DDXs in the sediments. The DDD/DDE ratios responded well to the anaerobic conditions in the sediments that were caused by algal blooms after the late 1970s in the western lake area. This suggests that the algae-derived organic matter was an important factor and served as a biomarker of eutrophication and also affected the DDX residues and lifecycle in the lake ecosystem. Graphical abstract: Highlights: Primary DDX sources in Lake Chaohu sediments were from historical usage of technical DDT. The p, p′-DDE and p, p′-DDD were predominant components of DDXs in surface and core sediments. Parent DDT compounds were still detectable in the sediment cores after the late 1930. Algae-derived organic matters affected strongly DDXs' residues, composition and distributions. DDD/DDE ratios well-replied anaerobic conditions in the sediments caused by mass algal blooms. Abstract : The residues, compositions and distributions of DDT-related contaminants in sediments were significantly affected by algae-derived organic matter.